Low-velocity impact damage characteristics and structural optimization of metal and CFRP through-thickness reinforcement connection structures - ZHAO Kunpeng; ZHENG Huilong; KANG Zhenya; ZHANG Saile; DONG Haibin (Cailiao gongcheng)
To improve the impact resistance of metal and composite material joint structures， a metal synapse structure was manufactured using metal laser selective melting technology. The structure was co-cured and molded with T300 twill woven carbon fiber-reinforced composite material （CFRP） to form a through-thickness reinforcement joint structure. The impact resistance of the synapse joint structure was verified through Charpy pendulum impact tests. Analysis and optimization of the synapse morphology were conducted based on CFRP damage patterns and impact absorption energy， as well as other influencing factors. Finite element simulations and comparative calculations were performed. The experimental results indicate that the penetration-enhanced joint method can prevent metal stress concentration and carbon fiber cutting caused by drilling holes. The impact absorption energy measures at 68.54 J， with a 216.1% improvement compared to the bolted connections. Increasing the height of the synapses effectively inhibits the composite material impact delamination. The synapse feature size and synapse array density affect internal defects in the composite material. With increasing synapse feature size and synapse array density，the impact absorption energy first increases to a point and then decreases. Finite element simulations based on synapse feature size variations showed that the simulation results deviated from the experimental results by less than 17%， and the damage form is highly consistent.